Map of Sky Brightness over Greater Bandung and the Prospect of Astro-Tourism - Rhorom Priyatikanto; Agustinus Gunawan Admiranto; Gerhana Puannandra Putri; Elyyani Elyyani; Siti Maryam; Nana Suryana (Indonesian Journal of Geography, 2019)
In this paper, result of moving campaigns of night sky brightness measurement over Greater Bandung area is reported. Though the campaigns were not commenced in ideal condition in terms of cloud cover and moon light contamination, the result is quite convincing. The obtained value of sky brightness range from ~17 mpsas at downtown region to ~20 mpsas at Haurgombong, Sumedang which is more than 30 km away from the city center. It is in agreement with months-length stationary measurements of sky brightness over Bandung, Lembang, and Sumedang. This result can be combined with nighttime satellite imagery from Defense Meteorological Satellite Program Operational Linescan System (DMSP-OLS) to produce the map of sky brightness over Greater Bandung area. This map is important product for regional planning and discussing the prospect of astro-tourism.